Representasi Unsur Jawa dalam Film Ketika Cinta Bertasbih 1 (Analisis Semiotika Charles Sanders Peirce) - Ido Afriadi; Namira Fitria; Parlin Harbet; Sanika Sembiring (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study examines Javanese cultural values found in the religious theatrical film Ketika Cinta Bertasbih 1. The research question addressed is what signs and meanings represent Javanese cultural values in the film. The approach used is semiotic analysis, focusing on symbolic meaning as the object of study. The research method applied is descriptive qualitative, which prioritizes depth of meaning over generalization of results. The data in this study consist of verbal and non-verbal texts. Verbal texts include spoken and written language, while non-verbal texts take the form of images and setting backgrounds contained in the film. Data were collected through an observation and note-taking technique, comprising: (1) watching the film, (2) recording relevant information, (3) collecting data through screenshots, (4) sorting the data, and (5) analyzing the data to draw conclusions. This study employs the semiotic framework of Charles Sanders Peirce, focusing on symbolic meaning as the unit of analysis. The findings reveal 4 images and narratives carrying symbolic meanings related to Javanese cultural elements, particularly through the use of Javanese vocabulary and settings located in Central Java.